Handbook on teacher portfolios for evaluation and professional development - Tucker, Pamela D. (Eye on Education, 2002)
This research-based book provides details on how educators can dramatically increase student achievement. It offers numerous experience-based ideas and strategies which can be applied to any school or district. This book will help you: establish a results-oriented focus on the curriculum, increase time-on-task and academic rigor for ALL students, provide a supportive accountability system for all staff members, identify and eliminate educational practices that lower student achievement, and introduce an achievement audit process that will increase student performance in any school or district.